Zambia : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Zambia. (IMF Staff Country Reports; Country Report, 2019)
This 2019 Article IV Consultation with Zambia highlights that the development strategy has targeted a rapid scale-up of public investment to address infrastructure needs. Recent efforts to adjust the fiscal stance have delivered some improvement in revenues; however, deficits have continued to rise following faster-than-budgeted execution of foreign-financed capital spending. With the anticipated growth dividend yet to materialize, the debt burden has risen sharply, resulting in currency weakness and rising local borrowing costs that have further pushed up the interest bill. A large, frontloaded, and sustained fiscal effort is needed to bring debt down to safer levels. This should include a moratorium on contracting new external non-concessional borrowing, steps to raise revenues, halt the build-up of domestic expenditure arrears, and to better prioritize public investment projects. Decisive steps forward to build confidence and deliver meaningful fiscal adjustment will be essential. Appropriately tight monetary policy also has a role to play in securing stability. Reserves should be replenished over the medium term. Steady attention to the business environment is also needed to support private investment going forward.